The likelihood of widespread accounting manipulation within an emerging economy. Issue 2 (10th February 2021) - Nguyen, Lan Anh; O'Connell, Brendan; Kend, Michael; Thi Pham, Van Anh; Vesty, Gillian
Abstract : Purpose: The study explores accountants' views of the likelihood of widespread accounting manipulation in the emerging economy, Vietnam. Applying the fraud triangle framework, we examine accountants' responses to management pressure, manipulation opportunities and perceptions of how they rationalize their decisions. Design/methodology/approach: The study uses an experimental methodology involving 592 Vietnamese accountants as participants. Post-experiment field interviews were conducted with eight highly experienced accountants. Findings: Our findings indicate that accounting manipulation is perceived to be common in Vietnam. The findings reveal that there is no differentiation between manipulation of accounting transactions with or without management pressure and no differentiation between collective gain or individual gain. Research limitations/implications: While the study focused on accountants' perceptions of accounting manipulation, these views may change over time. The impact of law reforms and the potential for prosecution under the force of law provisions could alter these perceptions. Practical implications: The study findings alert regulators, government authorities and auditors of the perceptions and views in relation to accounting manipulation and the potential for fraud in Vietnam. Auditors could use help from forensic specialists to uncover unethical behaviors identified in this study. Originality/value: The fraud triangle framework is used to shed light on fraud through the examination of accounting manipulation in Vietnam. We contribute to the relevant accounting literature with insights into accountants' motivations toward conducting questionable accounting transactions. The contributions we make draw attention to preconceptions of Asian societies; in particular, accounting actions to motivate collectivist gains. While we shed further light on fraudulent accounting, we conclude that the fraud triangle framework does not necessarily articulate fraud well in relation to accounting manipulation in emerging economies.